PENINGKATAN HASIL BELAJAR MELALUI STRATEGI PEMBELAJARAN LANGSUNG (DIRECT INSTRUCTION) MATA PELAJARAN BAHASA INDONESIA SDN 167644 KOTA TEBING TINGGI - Rohani . (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2015)
ABSTRACT This aim of this research is to know improvment of  learning result on Indonesian language subject  through direct instruction strategy. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class I, SDN 167644 Tebing Tinggi which amounted to 33 students. This study used a qualitative descriptive analysis technique. The results showed that the use of direct instruction strategy of Indonesian language subjects can improve student learning result characterized by increased mastery learning students, namely pre-cycle (69,69%), the first cycle (78,78%), cycle II (90,90 %) and complete learn the clasical equal to 90,90 %.   Key word : direct instruction, language, learning result